2016
DOI: 10.1016/j.jviromet.2016.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Cross-subtype detection of HIV-1 using reverse transcription and recombinase polymerase amplification

Abstract: A low complexity diagnostic test that rapidly and reliably detects HIV infection in infants at the point of care could facilitate early treatment, improving outcomes. However, many infant HIV diagnostics can only be performed in laboratory settings. Recombinase polymerase amplification (RPA) is an isothermal amplification technology that can rapidly amplify proviral DNA from multiple subtypes of HIV-1 in under twenty minutes without complex equipment. In this study we added reverse transcription (RT) to RPA to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 39 publications
(69 reference statements)
1
36
0
Order By: Relevance
“…RPA has the ability to tolerate mismatches, and the highest mismatch tolerability reported so far is nine nucleotide base pairs across the primer and probe binding sites. [82][83][84][85][86][87][88][89] Studies also showed that the mismatches at the 5′-end or centre of primers only mildly affect the RPA reaction, but mismatches located at the 3′-end of primers significantly affect the reaction. 84,86 This is consistent with the RPA reaction mechanism (see section 2.2), since the polymerase extends the primers and probe (once cleaved) from the 3′-terminus.…”
Section: Tolerability To Mismatches Inhibitors and Background Dnamentioning
confidence: 99%
“…RPA has the ability to tolerate mismatches, and the highest mismatch tolerability reported so far is nine nucleotide base pairs across the primer and probe binding sites. [82][83][84][85][86][87][88][89] Studies also showed that the mismatches at the 5′-end or centre of primers only mildly affect the RPA reaction, but mismatches located at the 3′-end of primers significantly affect the reaction. 84,86 This is consistent with the RPA reaction mechanism (see section 2.2), since the polymerase extends the primers and probe (once cleaved) from the 3′-terminus.…”
Section: Tolerability To Mismatches Inhibitors and Background Dnamentioning
confidence: 99%
“…PCR assays are difficult to implement in POC devices due to the significant power demands of thermocycling and the need for highly purified nucleic acids. Other options may include isothermal amplification techniques, such as loop-mediated isothermal amplification (LAMP) (84,85), helicase dependent amplification (86), and recombinase polymerase amplification (87). Isothermal assays do not require thermal cycling and therefore have reduced power demands and require less time for amplification.…”
Section: Technologies To Advance Next-generation Testsmentioning
confidence: 99%
“…The RPA reaction can tolerate a few base mismatches between the template and the primers or the probe (Daher, Stewart, Boissinot, Boudreau, & Bergeron, 2015; Lillis et al., 2016). This feature left us some room to modify the sequences of the primers and the probe.…”
Section: Resultsmentioning
confidence: 99%